2021
DOI: 10.1021/acsabm.1c00004
|View full text |Cite|
|
Sign up to set email alerts
|

Injectable and Degradable PEG Hydrogel with Antibacterial Performance for Promoting Wound Healing

Abstract: Injectable and degradable PEG hydrogel was prepared via Michael-type addition between cross-linking monomer 4-arm-PEG-MAL and two cross-linkers of hydrolysis degradable PEG-diester-dithiol and non-degradable PEG-dithiol, and it had a porous structure with the uniform pore size. The biocompatibility assays in vitro indicated that PEG hydrogel had excellent biocompatibility and can be degraded naturally without leading to any negative impact on cells. The results of antibacterial experiments showed that PEG hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 48 publications
1
50
0
Order By: Relevance
“…The scratch assay was performed according to previous reports [ 38 , 39 ]. 5 × 10 4 cells were seeded on a 24-well plate and incubated until 80% confluency.…”
Section: Methodsmentioning
confidence: 99%
“…The scratch assay was performed according to previous reports [ 38 , 39 ]. 5 × 10 4 cells were seeded on a 24-well plate and incubated until 80% confluency.…”
Section: Methodsmentioning
confidence: 99%
“…Peg or Ch has some beneficial role in tissue regeneration because they promote various cellular functions, for example, migration, adhesion, and proliferation [15,[57][58][59][60]. Furthermore, Peg, B, and Ch have an antimicrobial activity that reduces chances of infection and improves healing in the wound area [61][62][63]. us, it can be said that if the stability of Peg, B, or Ch maintains perfectly, in comparison with other hybrid composite hydrogels, these three composite hydrogels (X : Ge : Peg : Ch : G, X : Ge : B : Peg : G, and X : Ge : B : Peg : Ch : G) can largely perform in terms of possible wound healing.…”
Section: Wound Contraction Rate In Albino Wistar Ratmentioning
confidence: 99%
“…Physical cross-linking Ionic interaction [47,69,83,84,85,134] Hydrogen bonding [42,48,86] Self-assembly [97,152,170] Chemical cross-linking Schiff base reaction [41,70,88,115,148] Michael addition reaction [42,89,90] Free radical polymerization [41,43,69,91,64,173] Click chemistry [95,96,97] Enzyme cross-linking [54,99,100] Therefore, the design of green and non-toxic cross-linking agents and initiators is the focus of future research.…”
Section: Cross-linkingmentioning
confidence: 99%
“…It is characterized by high efficiency, high selectivity, without a large number of by-products, adding catalysts and coupling agents. Liu et al [89] reported an injectable PEG hydrogel based on Michael addition reaction between 4-arm-PEG-MAL and two cross-linkers of PEG-diesterdithiol and PEG-dithiol. PEG hydrogel could promote the process of wound healing and show great potential in the application for wound healing.…”
Section: Chemical Cross-linkingmentioning
confidence: 99%
See 1 more Smart Citation